Reliability Analysis of Reinforced Concrete Beams Subjected to Bending Using Different Methods and Design Codes. Issue 2 (1st May 2017) - García-Soto, Adrián-David; Hernández-Martínez, Alejandro; Valdés-Vázquez, Jesús-Gerardo
Abstract: Implicit reliability levels of reinforced concrete beams (RCB) vary depending on the employed design code and should ideally be related to the societal and geographical environment where the code is used. In this study, reliability analysis of RCBs subjected to bending using different methods and codes is carried out. The point estimate method (PEM), developed long time back by structural engineers, is still being used by engineers from different fields. In the PEM only the probabilistic moments of the random variables are required, but the resulting moments of the limit state function (LSF) have to be fitted to a probability density function (PDF) to obtain reliability levels. Approximating the moments of the LSF to a PDF is a long discussed problem still being investigated. In the current study, a very simple alternative by using a combined approach (including the PEM) and considering a well-known PDF is proposed. The results are in good agreement with those computed using other widely employed methods. The combined method is a very valuable option to determine reliability levels when a closed form of the LSF is not available.